Work Safety Management for Optimization Production Process - Rodrigues da Silva, Jacks; Barbosa de Alencar, David; Tregue Costa, Alexandra Priscilla; Estanislau Sanches, Antônio (International Journal for Innovation Education and Research, 2019)
The safety at work of employees is not always viewed with due importance. However, with the help of technology, such as E-social, the government system that organizes companies to communicate in a unified way as information for their employees, it executes with whom employers comply with strict safety standards. The main objective of this article is to demonstrate that occupational safety management improves accident rates in the company through actions on enforcement methods that are the basic causes of accidents. What's more, quality, management, costs and other values ​​are better through behavioral changes. Within the Thematic service, we seek or develop conscientious and motivated employees, as a safe environment must be in place to support safe working employees. Therefore, after the implant or safety management system, you can reduce a satisfactory reduction of work accidents and get good results in the production process.